Analisis Dampak Kenaikan Tarif Pajak Pertambahan Nilai (PPN) terhadap Daya Beli Masyarakat di Kabupaten Sidoarjo - Alfiatus Fadjar Kurnaini; Imelda Dian Rahmawati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research aims to analyze the impact of increasing Value Added Tax (VAT) rates on people's purchasing power in Sidoarjo Regency. This research uses qualitative methods with a focus on understanding social phenomena from the participant's perspective, combining a case study approach and interview techniques with informants. Research identifies that the increase in VAT rates from 10% to 11% in April 2022, has affected the prices of goods and services. This has had a negative impact on people's purchasing power, especially low and middle income groups who have seen the prices of their basic necessities increase. Not only the public as consumers, business actors also face challenges in adapting to the additional costs that must be paid to the government. Interview results show that people respond to rising prices by reducing purchases of goods and services, and looking for cheaper alternatives. This reflects the social impact of fiscal policies such as increases in VAT rates, which can slow economic growth and exacerbate social inequality if not managed wisely. This research contributes to a deeper understanding of the impact of tax policy on communities and businesses at the local level, with the hope of providing guidance for more inclusive and sustainable policies in the future.